A Genome‐Wide Linkage Scan for Quantitative Trait Loci Influencing the Craniofacial Complex in Humans (Homo sapiens sapiens) - Sherwood, Richard J.; Duren, Dana L.; Mahaney, Michael C.; Blangero, John; Dyer, Thomas D.; Cole, Shelley A.; Czerwinski, Stefan A.; Chumlea, WM. Cameron; Siervogel, Roger M.; Choh, Audrey C.; Nahhas, Ramzi W.; Lee, Miryoung; et al. (Anatomical record (Hoboken, N.J. : 2007), 2011)
The genetic architecture of the craniofacial complex has been the subject of intense scrutiny because of the high frequency of congenital malformations. Numerous animal models have been used to document the early development of the craniofacial complex, but few studies have focused directly on the genetic underpinnings of normal variation in the human craniofacial complex. This study examines 80 quantitative traits derived from lateral cephalographs of 981 participants in the Fels Longitudinal Study, Wright State University, Dayton, Ohio. Quantitative genetic analyses were conducted using the Sequential Oligogenic Linkage Analysis Routines analytic platform, a maximum‐likelihood variance components method that incorporates all familial information for parameter estimation. Heritability estimates were significant and of moderate to high magnitude for all craniofacial traits. Additionally, significant quantitative trait loci (QTL) were identified for 10 traits from the three developmental components (basicranium, splanchnocranium, and neurocranium) of the craniofacial complex. These QTL were found on chromosomes 3, 6, 11, 12, and 14. This study of the genetic architecture of the craniofacial complex elucidates fundamental information of the genetic architecture of the craniofacial complex in humans. Anat Rec, 2011. © 2011 Wiley‐Liss, Inc.